1999
DOI: 10.1111/j.1467-842x.1999.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between alcohol related hospital admissions and alcohol consumption in Victoria: Influence of socio-demographic factors

Abstract: Objective: To examine the cross-sectional ecologic associations between apparent per-capita alcohol consumption, alcoholrelated hospital admission rates, and the distributions of socio-demographic factors for people residing in 76 Local Government Areas (LGAs) in Victoria, during the 1995-1 996 fiscal year. Method: Visitor-adjusted per-capita alcohol consumption was obtained from wholesale sales data from the Liquor Licensing Commission Victoria. Alcoholrelated hospital admission rates were extracted from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
2
19
2
Order By: Relevance
“…One example is a study from Australia in which positive co-variation was established between per capita consumption and an index of alcohol-related hospital admission rates [33]. On the basis of a simple correlation analysis of data for the period 1970 -2000, a positive temporal co-variation between alcohol consumption and morbidity from alcoholism and alcohol psychosis was also obtained for Belarus [34].…”
Section: Liver Cirrhosis and Alcohol-related Diseasesmentioning
confidence: 99%
“…One example is a study from Australia in which positive co-variation was established between per capita consumption and an index of alcohol-related hospital admission rates [33]. On the basis of a simple correlation analysis of data for the period 1970 -2000, a positive temporal co-variation between alcohol consumption and morbidity from alcoholism and alcohol psychosis was also obtained for Belarus [34].…”
Section: Liver Cirrhosis and Alcohol-related Diseasesmentioning
confidence: 99%
“…For example, reports from the National Hospital Discharge Survey found that older adults have more alcohol-related medical problems as compared with their younger counterparts (65.1 vs. 60.4 per 10,000 population; Stinson, Dufour, & Bertolucci, 1989 Adams et al (1993) reported a prevalence rate of 48.2 hospitalizations per 10,000 Medicare beneficiaries. A similar study conducted by Jonas et al (1999) found that annual alcohol-related hospital admission rates ranged from 8 to 37 per 10,000 residents.…”
Section: Introductionmentioning
confidence: 76%
“…11,6 This method found currency among researchers and many works have followed the lead set by English et al, 6 including several recent publications. 2,4,32 However, new work by the AIHW, in particular, has recently recharged the debate about whether an abstinence-based contrast is in fact preferable to a low level of consumption comparison. For instance, in their publication Burden of Disease and Injury in Australia, Mathers and colleagues 5 separately estimated the 'benefits' of an y alcohol consumption (i.e.…”
Section: Indeed the Who's International Guidelines For Monitoring Almentioning
confidence: 99%